Autologous costal chondral transplantation and costa-derived chondrocyte implantation: emerging surgical techniques. (September 2019) - Gao, Youshui; Gao, Junjie; Li, Hengyuan; Du, Dajiang; Jin, Dongxu; Zheng, Minghao; Zhang, Changqing
It is a great challenge to cure symptomatic lesions and considerable defects of hyaline cartilage due to its complex structure and poor self-repair capacity. If left untreated, unmatured degeneration will cause significant complications. Surgical intervention to repair cartilage may prevent progressive joint degeneration. A series of surgical techniques, including biological augmentation, microfracture and bone marrow stimulation, autologous chondrocyte implantation (ACI), and allogenic and autogenic chondral/osteochondral transplantation, have been used for various indications. However, the limited repairing capacity and the potential pitfalls of these techniques cannot be ignored. Increasing evidence has shown promising outcomes from ACI and cartilage transplantation. Nevertheless, the morbidity of autologous donor sites and limited resource of allogeneic bone have considerably restricted the wide application of these surgical techniques. Costal cartilage, which preserves permanent chondrocytes and the natural osteochondral junction, is an ideal candidate for the restoration of cartilage defects. Several in vitro and in vivo studies have shown good performance of costal cartilage transplantation. Although costal cartilage is a classic donor in plastic and cosmetic surgery, it is rarely used in skeletal cartilage restoration. In this review, we introduce the fundamental properties of costal cartilage and summarize costa-derived chondrocyte implantation and costal chondral/osteochondral transplantation. We will also discuss the pitfalls and pearls of costal cartilage transplantation. Costal chondral/osteochondral transplantation and costa-based chondrocytotherapy might be up-and-coming surgical techniques for recalcitrant cartilage lesions.